Mechanochemical tools for polymer materials. (5th February 2021) - Chen, Yinjun; Mellot, Gaëlle; van Luijk, Diederik; Creton, Costantino; Sijbesma, Rint P.
Abstract : This review aims to provide a field guide for the implementation of mechanochemistry in synthetic polymers by summarizing the molecules, materials, and methods that have been developed in this field. Abstract : Mechanochemistry provides a unique approach to investigate macroscopic deformation, failure and healing of polymer materials. The development of mechanophores – molecular units that respond to mechanical force – has been instrumental in the success of this endeavor. This review aims to provide a critical evaluation of the large variety of mechanophores reported in literature, and to assess the molecular and macroscopic factors that determine their activation. Applications in materials science are highlighted, and challenges in polymer mechanochemistry are discussed.